Transforming English rural society : the Verneys and the Claydons, 1600-1820 - Broad, John, 1945- (Cambridge studies in population, economy, and society in past time, 2004)
John Broad explores the rise and fall of the Verney family of Middle Claydon, Buckinghamshire. He shows how the family were impelled by a strong dynastic imperative, how they managed their estates to maximise income and transformed three local villages into 'open' and 'closed' parishes.